Correlates of Food–Energy–Water Nexus Awareness Among the American Public*. (6th February 2019) - Hannibal, Bryce; Portney, Kent
Abstract : Objective: Recently, much research in the physical sciences has been dedicated to identifying a nexus or connection between water, energy, and food. This research agenda, however, has not been sufficiently examined in the social sciences. This article examines the extent to which individuals demonstrate awareness of the three nexus elements: water–energy, energy–food, and food–water. Methods: We use three awareness indexes as dependent variables and varying sociodemographic characteristics and aspects of environmental concern as predictors in the statistical analysis. Results: Our results suggest that there are some patterned or systematic correlates with the nexus elements, although relationships do not always turn out as anticipated. Indeed, explanations of nexus awareness do not follow previously studies' explanations of environmental concern, and vary depending on which elements of the nexus are analyzed. Conclusion: We conclude with suggestions to raise awareness of the connections between natural resources among all populations. Such awareness will promote sustainable societies and reduce environmental inequality and issues of environmental justice